Cultural resilience, religion, and economic recovery: Evidence from the 2005 hurricane season - Iftekhar Hasan; Stefano Manfredonia; Felix Noth (Halle Institute for Economic Research (IWH), 2021)
This paper investigates the critical role of religion in the economic recovery after high-impact natural disasters. Exploiting the 2005 hurricane season in the southeast United States, we document that establishments in counties with higher religious adherence rates saw a significantly stronger recovery in terms of productivity for 2005-2010. Our results further suggest that a particular religious denomination does not drive the effect. We observe that different aspects of religion, such as adherence, shared experiences from ancestors, and institutionalised features, all drive the effect on recovery. Our results matter since they underline the importance of cultural characteristics like religion during and after economic crises.
Keywords: E23; E32; Z12; 330; establishment-level productivity; natural disasters; recovery; religion